Hedgehog signaling activation in human cancer and its clinical implications - Xie, Jingwu (Springer, 2011)
Despite significant progress in our understanding of cancer biology, cancer continues to be the second cause of human mortality. The remarkable responses of cancer patients to inhibitors to the hedgehog signaling pathway implies a promising novel approach to treat cancer. As a result, understanding the role of hedgehog signaling in cancer is critically important for novel cancer therapeutics. The hedgehog pathway, initially discovered by two Nobel laureates Drs. E. Wieschaus and C. Nusslein-Volhard in Drosophila, is a major pathway regulating cell differentiation, tissue polarity, stem cell maintenance and cell proliferation. It is known by now that activation of this pathway occurs in a variety of human cancer, including basal cell carcinomas (BCCs), medulloblastomas, leukemia, gastrointestinal, lung, ovarian, breast and prostate cancers. Even more exciting is the discovery and synthesis of specific signaling antagonists for the hedgehog pathway, which have significant clinical implications in novel cancer therapeutics. To provide the most up-to-date information on recent development in this exciting research area, we have invited experts in hedgehog signaling field to summarize major advances made in the last few years on hedgehog signaling mechanisms, activation of the pathway in various human cancer types, potential antagonists for hedgehog signaling inhibition and their clinical implications for human cancer treatment. Authors of the book have also highlighted current challenges in our efforts to translate the basic biology into clinic. This book provides insightful views suitable for graduate students, medical students, undergraduate students, basic and clinical scientists, cancer patients as well as the general public.